Manajemen Perubahan Budaya Sekolah - Hendro Widodo (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
Change ability of a school is determined by the extent to which the school’s member have power in carrying and managing change. The changes may occur within the school environment or outside the school that influence the changes toward the school itself. The shifts that occur within the school may not necessarily alter the school thoroughly, but usually preceded by a process of cultural transformation. The success of school’s cultural shifts depends on the change management applied. Therefore, any changes that happen requires a change management so that the alteration at the school is the result of school’s community values and directed from the community itself, so the impact would lead to a positive change.